High‐resolution MRI encoding using radiofrequency phase gradients. (6th September 2013) - Sharp, Jonathan C.; King, Scott B.; Deng, Qunli; Volotovskyy, Vyacheslav; Tomanek, Boguslaw
Abstract : Although MRI offers highly diagnostic medical imagery, patient access to this modality worldwide is very limited when compared with X‐ray or ultrasound. One reason for this is the expense and complexity of the equipment used to generate the switched magnetic fields necessary for MRI encoding. These field gradients are also responsible for intense acoustic noise and have the potential to induce nerve stimulation. We present results with a new MRI encoding principle which operates entirely without the use of conventional B 0 field gradients. This new approach – 'Transmit Array Spatial Encoding' (TRASE) – uses only the resonant radiofrequency (RF) field to produce Fourier spatial encoding equivalent to conventional MRI. k ‐space traversal (image encoding) is achieved by spin refocusing with phase gradient transmit fields in spin echo trains. A transmit coil array, driven by just a single transmitter channel, was constructed to produce four phase gradient fields, which allows the encoding of two orthogonal spatial axes. High‐resolution two‐dimensional‐encoded in vivo MR images of hand and wrist were obtained at 0.2 T. TRASE exploits RF field phase gradients, and offers the possibility of very low‐cost diagnostics and novel experiments exploiting unique capabilities, such as imaging without disturbance of the main B 0 magnetic field. Lower field imaging (<1 T) and micro‐imaging are favorable application domains as, in both cases, it is technically easier to achieve the short RF pulses desirable for long echo trains, and also to limit RF power deposition. As TRASE is simply an alternative mechanism (and technology) of moving through k space, there are many close analogies between it and conventional B 0 ‐encoded techniques. TRASE is compatible with both B 0 gradient encoding and parallel imaging, and so hybrid sequences containing all three spatial encoding approaches are possible. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We present an MRI principle which operates entirely without the use of conventional field gradients. This new approach uses only the resonant radiofrequency (RF) field to produce Fourier spatial encoding equivalent to conventional MRI. High‐resolution two‐dimensional‐encoded in vivo MR images have been obtained. This approach exploits RF field phase gradients and offers the possibility of very low‐cost diagnostics and novel experiments exploiting unique capabilities, such as imaging without disturbance of the main magnetic field.